Atelier de renforcement de capacite sur la prise de decision en lien avec les services d’information climatique - Thiaw, Moussa; Ndiaye, Diabel; Worou, Nadine; Hachim Said, Shakira; Diedhiou, Lamine (International Livestock Research Institute, 2025)
The diagnostic workshop held in Thiès on 29 and 30 July 2025 brought together around thirty stakeholders (ANACIM, GTP, local authorities, researchers, media and CGIAR partners) to discuss the promotion of climate information services (CIS) in Senegal. Discussions confirmed that many producers already benefit from CIS thanks to AICCRA, while highlighting major challenges: technical language, poor accessibility and lack of coordination. Participants proposed concrete solutions, including translation into local languages, diversification of distribution channels (WhatsApp, radio, SMS), institutionalisation of GTPs and integration of CIS into municipal plans. Testimonials from Fatick, Mandakaoul and Kaolack illustrated the direct impact of CIS on food security, resource management and community resilience. The workshop enabled participants to define a shared roadmap for transforming climate challenges into opportunities for sustainable local development. Through voices from the field, the workshop showed that climate services are no longer just scientific data, but an essential agricultural input capable of saving crops, protecting incomes and strengthening resilience. The stories from Fatick, Mandakaoul and Kaolack demonstrate that when properly disseminated, SICs become real levers for local transformation. The workshop thus embodied a strong conviction: together, researchers, communities and decision-makers can transform climate challenges into opportunities for a more secure and sustainable future.